Beyond the pandemic: Posttraumatic stress and its association with physical and mental health outcomes among older adults in Egypt – a cross-sectional study - El-Sayed, Mona Metwally; Abd-Elhay, Eman Sameh; Taha, Samah Mohamed; Wafik, Wagdia; Ahmed, Hala Awad; Alharbi, Ghala Abdullah; Hawash, Manal Mohammed (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: The COVID-19 pandemic has severely affected older adults worldwide, with the Egyptian geriatric population facing vulnerabilities due to limited healthcare access and cultural factors. Posttraumatic stress disorder (PTSD) following COVID-19 may significantly impact physical and mental health, yet data specific to older Egyptians are limited. Objective: This study aimed to assess the prevalence of PTSD and its association with physical and mental health outcomes among older adults in Egypt after COVID-19 infection. Methods: A cross-sectional study included 290 geriatric patients (≥60 years) recruited from outpatient clinics at two Egyptian university hospitals. Data collection took place over three months, from September to December 2023. PTSD symptoms were measured using the PTSD Checklist-Civilian Version (PCL-C), and physical and mental health were evaluated by the 12-item Short Form Health Survey (SF-12). Pearson correlation and multiple linear regression were used to analyze the relationships between PTSD and health outcomes, controlling for sociodemographic and clinical factors. Results: Moderate PTSD symptoms were present in 60.3% of participants, and 18.6% showed severe symptoms. Physical health (PCS mean = 31.97, SD = 6.66) and mental health (MCS mean = 32.54, SD = 13.34) scores were significantly reduced. PTSD symptom clusters, such as hyperarousal and avoidance, were negatively correlated with physical and mental health components (e.g., hyperarousal vs. PCS: r = -0.206, p <0.001). The regression model explained 59% of the variance in health outcomes (adjusted R² = 0.59). Higher PTSD symptom severity was associated with a small but statistically significant negative effect on health outcomes (B = -0.20, p = 0.033). Chronic disease status showed the largest negative association (B = -12.34, p <0.001), indicating a substantial impact on health. Age demonstrated a modest negative association (B = -0.15, p = 0.049), while gender and education were not significantly associated with health outcomes. Conclusion: Nearly four out of five older Egyptian adults experienced moderate to severe PTSD after COVID-19, and PTSD symptoms were significantly associated with poorer physical and mental health. Chronic illness emerged as the strongest determinant of health outcomes, with age showing a modest effect. These findings highlight the importance of culturally sensitive, trauma-informed nursing interventions that address both PTSD and chronic illness to improve the well-being of older adults.